Developmental correlates of age at first hospitalization in nonschizophrenic psychiatric patients - Glick, M.; Zigler, E.; Zigler, B. (Journal of Nervous and Mental Disease, 1985)
Age at first hospitalization, premorbid social competence, and developmental categorizations of symptomatology were examined in 228 male and 220 female patients in three diagnostic categories: Major affective disorder, neuroses, and personality disorder. High social competence patients were older at first hospitalization than low competence individuals. Younger first admission patients showed more symptoms in the action category and in the role orientation of turning against others. Older patients more frequently displayed symptoms of the thought variety and of turning against the self. Gender differences in age at first hospitalization were not found. With respect to all developmental variables examined, the results suggest that a broader view of prognosis proposed in research with schizophrenic patients is applicable to nonschizophrenic groups. © 1985 by The Williams & Wilkins Co.
Keywords: Adult; Age Factors; Female; Hospitalization; Human; Male; Marriage; Mental Disorders; Middle Age; Mood Disorders; Neurotic Disorders; Occupations; Personality Disorders; Prognosis; Role; Sex Factors; Social Adjustment; Support, Non-U.S. Gov't; Support, U.S. Gov't, P.H.S.; affective neurosis; age; central nervous system; clinical article; dept.psy; hospitalization; human; mental patient; neurosis; personality disorder; priority journal; psychological aspect; social aspect; sociology

The Need to Test Hypotheses About Paranoid Schizophrenia: Reply to Clementz and Sweeney - Glick, M.; Zigler, E. (American Psychologist, 1989)
Keywords: Depressive Disorder; Diagnosis, Differential; Human; Psychiatric Status Rating Scales; Schizophrenia, Paranoid; article; depression; dept.psy; differential diagnosis; human; paranoid schizophrenia; psychological aspect; rating scale

Inter-relationships among hospitalization measures of psychiatric outcome - Glick, M.; Marsh, A.; Zigler, E. (Journal of Nervous and Mental Disease, 1980)
In a diagnostically heterogeneous sample of 381 first admission male state hospital patients, no consistent correlations appeared among three commonly employed hospitalization measures of outcome. The possibility that psychiatric hospitalization may be a multidimensional criterion is considered and the implications for outcome research are discussed. © 1980 by The Williams & Wilkins Co.
Keywords: Follow-Up Studies; Hospitalization; Human; Length of Stay; Male; Mental Disorders; Models, Theoretical; Patient Readmission; Support, U.S. Gov't, P.H.S.; central nervous system; dept.psy; hospitalization; major clinical study; therapy

Premorbid social competence and the revolving door phenomenon in psychiatric hospitalization - Marsh, A.; Glick, M.; Zigler, E. (Journal of Nervous and Mental Disease, 1981)
The relation between premorbid social competence and length of initial hospitalization was examined in 381 male state hospital patients in four diagnostic categories: Schizophrenic, affective reaction, psychoneurotic, and personality disorder. A significant relation was discovered between diagnosis and outcome, with schizophrenic patients having the longest and personality disorder patients the shortest lengths of initial hospitalization. Premorbid social competence was related to outcome, as assessed both by length of initial hospitalization, and by whether the patient was rehospitalized. These two outcome measures were found to be positively related, thus supporting the developmental formulation that premorbid social competence is indicative generally of prognosis. The findings were employed to generate the inference that patients at differing levels of premorbid social competence require different treatment modalities. © 1981 by The Williams & Wilkins Co.
Keywords: Adult; Hospitals, Psychiatric; Human; Length of Stay; Male; Mental Disorders; Mood Disorders; Neurotic Disorders; Personality Disorders; Recurrence; Schizophrenia; Social Adjustment; central nervous system; dept.psy; major clinical study; mental hospital; personality disorder; schizophrenia; sociology